Three-Dimensional Genome Interactions Identify Potential Adipocyte Metabolism-Associated Gene STON1 and Immune-Correlated Gene FSHR at the rs13405728 Locus in Polycystic Ovary Syndrome - Cao, Can-hui; Wei, Ye; Liu, Rang; Lin, Xin-ran; Luo, Jia-qi; Zhang, Qiu-ju; Lin, Shou-ren; Geng, Lan; Ye, Si-kang; Shi, Yu; Xia, Xi (Frontiers in Endocrinology, 2021)
Background: rs13405728 was identified as one of the most prevalent susceptibility loci for polycystic ovary syndrome (PCOS) in Han Chinese and Caucasian women. However, the target genes and potential mechanisms of the rs13405728 locus remain to be determined. Methods: Three-dimensional (3D) genome interactions from the ovary tissue were characterized via high-through chromosome conformation capture (Hi-C) and Capture Hi-C technologies to identify putative targets at the rs13405728 locus. Combined analyses of eQTL, RNA-Seq, DNase-Seq, ChIP-Seq, and sing-cell sequencing were performed to explore the molecular roles of these target genes in PCOS. PCOS-like mice were applied to verify the expression patterns. Results: Generally, STON1 and FSHR were identified as potential targets of the rs13405728 locus in 3D genomic interactions with epigenomic regulatory peaks, with STON1 (P=0.0423) and FSHR (P=0.0013) being highly expressed in PCOS patients. STON1 co-expressed genes were associated with metabolic processes (P=0.0008) in adipocytes (P=0.0001), which was validated in the fat tissue (P<0.0001) and ovary (P=0.0035) from fat-diet mice. The immune system process (GO:0002376) was enriched in FSHR co-expressed genes (P=0.0002) and PCOS patients (P=0.0002), with CD4 high expression in PCOS patients (P=0.0316) and PCOS-like models (P=0.0079). Meanwhile, FSHR expression was positively correlated with CD4 expression in PCOS patients (P=0.0252) and PCOS-like models (P=0.0178). Furthermore, androgen receptor (AR) was identified as the common transcription factor for STON1 and FSHR and positively correlated with the expression of STON1 (P=0.039) and FSHR (P=4e-06) in ovary tissues and PCOS-like mice. Conclusion: Overall, we identified STON1 and FSHR as potential targets for the rs13405728 locus and their roles in the processes of adipocyte metabolism and CD4 immune expression in PCOS, which provides 3D genomic insight into the pathogenesis of PCOS.